Enhancement of Xanthan Production on Date Extract Using Response Surface Methodology - B.N. Farhadi, Ghazaleh; Khosravi-Darani, Kianoush; Naser Nejad, Bahram (Asian Journal of Chemistry, 2012)
Evaluation of process variables (concentration of carbon, nitrogen and phosphorus sources) impact on xanthan production by Xanthomonas campestris from date extract were investigated using response surface methodology. Batch fermentation was carried out at 28 ºC (cell growth phase, 24 h) and 32 ºC (gum production phase, 48 h) in the medium containing date extract, NH4NO3 and K2HPO4 as carbon, nitrogen and phosphorus sources, respectively. The main and interaction effects of three variables on xanthan production were studied using a face-centre composite design. A quadratic equation was fitted for gum production. Maximum xanthan concentration 14.61 g/L was obtained at 40, 9, 0.1 g/L carbon, phosphorous and nitrogen sources, respectively.